Synthesis, Photophysical Characterization, and Self-Assembly of Hexa-peri-hexabenzocoronene/Benzothiadiazole Donor–Acceptor Structure - Hu, Yunbin; Doessel, Lukas F.; Wang, Xiao-Ye; Mahesh, Sankarapillai; Pisula, Wojciech; De Feyter, Steven; Feng, Xinliang; Muellen, Klaus; Narita, Akimitsu (ChemPlusChem, 2017)
Hexa-peri-hexabenzocoronene (HBC) substituted by six benzothiadiazole (BTZ) units with ethynylene bridges is synthesized as a new donor–acceptor (D–A) motif. The C≡C bridges significantly reduce the dihedral angles between HBC and BTZ, and thus, lead to a planar molecular conformation as predicted by density functional theory calculations. The optoelectronic properties are investigated by UV/Vis absorption and emission spectroscopies with absorption and emission maxima at 424 and 650 nm, respectively, demonstrating the tunable electronic structures of HBC through the attachment of electron-withdrawing BTZ units. Two-dimensional wide-angle X-ray scattering analysis shows that the molecules self-assemble into liquid-crystalline columns with high stability over a wide temperature range. Scanning tunneling microscopy reveals the formation of ordered bilayers of the D–A molecules with star-shaped structures.
CRIS-Team Scopus Importer:2023-03-20
Keywords: benzothiadiazole; charge transfer; donor–acceptor systems; hexa-peri-hexabenzocoronene; optoelectronic properties